Pengembangan Media Ludo Geometri (DORI) pada Fisik Motorik Anak Usia Dini - Juniarti, Yenti (Al-Athfal: Jurnal Pendidikan Anak, 2019)
This study aims to develop media ludo geometry (DORI) in children in Kiddie Care PAUD, due to the low ability of children to perform gross motor skills. This study uses a research and development approach. While the development model used is the Research & Development (R&D) development model according to Borg & Gall. The results of this study are the development of DORI media (Ludo Geometry), there are several aspects that arise besides physical activity, namely cognitive where children are required to think creatively, express ideas in their minds, on social aspects children mutually interact and discuss in search of strategies games, and in the language aspect of students or children become skilled in communication and dialogue, other results such as children feel the game using this DORI media such as sports while playing, and playing while learning. Conclusion that gross motor skills of early childhood are able to develop well in cognitive, social emotional and language aspects by using Ludo Geometry media.